AB EVALUATION OF LEARNING ATTITUDE AND ACHIEVEMENT OF SMALL AND MEDIUM SCALE ENTERPRISES IN NIGER STATE NIGERIA - Abdulrazak Mohammed (PODIUM)
A study was done in Niger State, Nigeria, to evaluate the achievement and learning attitude of small and medium-sized enterprises (SMEs). The population comprises of 1,045 registered SME’s of which 377 were sample randomly for the study in Niger State and were given a structured questionnaire to answer as part of the survey design used in this study. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used for data analysis. The results of the study revealed a strong and favorable relationship between SMEs' performance and their learning attitude. As a result, the findings imply that encouraging a good learning attitude may help to solve the under performance issue among SMEs in Niger State, which is a concern for both stakeholders and residents. The report concludes by recommending that the Niger State government routinely provide seminars and workshops for the state's registered SMEs in cooperation with pertinent regulatory organizations like SMEDAN and Ministry of Commerce and industry in the state. The main goals of these seminars have to be to disseminate information about shifting consumer demands, rival tactics, market dynamics, and technological breakthroughs. By doing this, SMEs can become more innovative and provide goods and services that surpass those of rivals, which will improve their standing in the state.